Gamma-Fe composite Fe-N / O@C catalyst for advanced oxidation treatment of wastewater and preparation method thereof
Patent Information
- Application Number
- CN202410083869.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-01-19
- Publication Date
- 2026-10-30
- Estimated Expiration
- 2044-01-19
AI Technical Summary
[0003]为了克服现有技术存在的不足,解决传统Fe-N催化剂因对称配位结构而引起的中间产物在活性位点上吸附过强从而限制催化活性的问题,本发明的目的是提供一种γ-Fe复合Fe-N/O@C催化材料及其制备方法,并提供该催化剂材料用于废水高级氧化处理的方法
[0032](1)本发明通过Fe、O共掺杂ZIF-8纳米材料的热解制备了一系列Fe-N/O@C催化剂,所获得的Fe-N/O@C用于活化PMS以降解有机污染物时,发现Fe-N/O配位结构比FeNx和纯N掺杂碳表现出更好的催化性能,得益于N2-Fe-O2配位构型的单原子Fe及γ-Fe物种的协同作用,所制备的Fe-N/O@C在60分钟内表现出99.4%的最高污染物去除效率,计算得到的反应速率是Fe-N@C催化剂的2.29倍。此外,Fe-N/O@C在pH=2.0~10.0的宽pH范围内表现出良好的催化活性,在实际废水处理中具有良好的应用前景。
Smart Images

Figure CN118122360B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the fields of chemical materials and pollutant treatment, specifically to a method for preparing a γ-Fe composite Fe-N / O@C catalytic material and its application in advanced oxidation treatment of wastewater. Background Technology
[0002] Advanced oxidation technology is a highly efficient and promising wastewater treatment technology that can be used to treat various polluted water bodies. Compared with traditional advanced oxidation technologies (such as Fe), 2+ Persulfate (PSA) technology for degrading recalcitrant organic compounds (AOPs) exhibits many excellent properties and has broad application prospects in environmental remediation. Among these, heterogeneous catalysts have received considerable attention in recent years for their high catalytic efficiency, good stability, and easy recovery. Incorporating Fe-SACs into carbon-based materials can achieve good oxidant activation performance, and in most studies, isolated single Fe-N... x The molecule is considered the active site that plays a major role. Among them, the symmetrical structure of Fe-N4 results in a low formation energy and is easy to synthesize, thus attracting the attention of researchers. For example, Gao et al. prepared a single-atom catalyst with Fe-N4 coordination configuration by chelating sodium citrate, glucose, melamine, and Fe ions (Unraveling the High-Activity Origin of Single-Atom Iron Catalysts for Organic Pollutant Oxidation via Peroxymonosulfate Activation, Environ. Sci. Technol., 2021, 55, 8318-8328.). However, recent studies have shown that the symmetrically coordinated N atoms around the Fe site can lead to excessive adsorption of intermediates at the active site, thus limiting its catalytic activity (Engineering Unsymmetrically Coordinated Fe Sites via Heteroatom Pairs Synergetic Contribution for Efficient Oxygen Reduction. Small, 2023: 2304303.). Therefore, the preparation of novel catalysts with synergistic effects of Fe nanoparticles and single-atom iron sites to enhance their practicality is of great practical significance. Summary of the Invention
[0003] To overcome the shortcomings of existing technologies and solve the problem that the intermediate products of traditional Fe-N catalysts are adsorbed too strongly at the active sites due to the symmetrical coordination structure, thus limiting the catalytic activity, the present invention aims to provide a γ-Fe composite Fe-N / O@C catalytic material and its preparation method, and to provide a method for using the catalytic material for advanced oxidation treatment of wastewater.
[0004] Compared to nitrogen (N) atoms, oxygen (O) atoms have higher electronegativity. Incorporating O into the CN structure directly alters the planar structure of aromatic compounds, thereby changing the surrounding electronic structure. Therefore, this invention utilizes the strong interaction between ferrous gluconate and the zeolite framework to dope the Fe-O structure in ferrous gluconate to the edge NC sites, forming an FNO coordination structure. Introducing O atoms into the Fe-N4 structure to form a Fe-O structure disrupts the original Fe-N4 symmetry, weakens the adsorption of intermediate products at active sites, and simultaneously lowers the oxidation state of the central Fe atom, increasing the Fe... 3+ / Fe 2+ This improves the catalytic activity by enhancing the recycling capacity. Simultaneously, by doping with highly conductive metal nanoparticles (MNPs), the electronic structure of the adjacent carbon support can be effectively modulated through interfacial electron transfer, thereby enhancing the catalyst's catalytic ability.
[0005] To achieve the above objectives, the present invention adopts the following technical solution.
[0006] A method for preparing a γ-Fe composite Fe-N / O@C catalyst includes the following steps:
[0007] S1. Synthesis of Fe-ZIF-8 precursor, the specific steps are as follows:
[0008] (1) Dissolve ferrous gluconate and zinc nitrate hexahydrate in methanol and label it as solution A;
[0009] (2) Dissolve 2-methylimidazole in methanol in another beaker and label it as solution B;
[0010] (3) Stir solutions A and B separately with glass rods. After both are completely dissolved, pour solution B into solution A and stir on a magnetic stirrer for 1 to 4 hours. After stirring, let the solution stand for 12 to 24 hours. Wash with methanol, centrifuge to precipitate, and then vacuum dry at 60 to 80°C for 12 to 24 hours to obtain the Fe-ZIF-8 precursor.
[0011] S2, Zn in ZIF-8 is removed by pyrolysis. 2+ Evaporation occurs, and then Fe enters and forms coordination sites to achieve uniform Fe doping. The specific operation steps are as follows:
[0012] The obtained Fe-ZIF-8 precursor was placed in a quartz boat, which was then placed in a tube furnace. Nitrogen gas was then introduced into the tube furnace, and the temperature was increased to 700-900℃ at a heating rate of 2-10℃ / min and maintained for 2-4 hours.
[0013] S3. The Fe-N / O@C catalyst is obtained by removing unstable Fe species through acid washing. The specific operation steps are as follows:
[0014] After the tube furnace cools down, the sample is taken out and soaked in 0.5-2M HCl for 1-6 hours. After centrifugation, it is washed with methanol and then dried in a vacuum drying oven at 60-80℃ for 12-24 hours to obtain the Fe-N / O@C catalyst.
[0015] Preferably, in step S1(1), the molar ratio of ferrous gluconate and zinc nitrate hexahydrate is 1:70 to 150, and more preferably 1:70.
[0016] Preferably, in step S1(1), the molar ratio of zinc nitrate hexahydrate to methanol is 1:150 to 600, and more preferably 1:300.
[0017] Preferably, in step S1(2), the molar ratio of 2-methylimidazole to methanol is 1:8 to 40, and more preferably 1:15.
[0018] More preferably, in step S1(3), the stirring time is 2 hours.
[0019] More preferably, in step S1 (3), the settling and aging time is 20 hours.
[0020] More preferably, in step S1(3), the vacuum drying temperature is 60°C and the vacuum drying time is 20h.
[0021] More preferably, in step S2, the heating rate is 5°C; the calcination temperature is 800°C; and the calcination time is 2 hours.
[0022] In a further preferred embodiment, in step S3, the tubular furnace is cooled to room temperature at a rate of 5°C / min.
[0023] More preferably, in step S3, the sample is soaked in 0.5M hydrochloric acid for 2 hours.
[0024] More preferably, in step S3, the vacuum drying temperature is 60°C and the vacuum drying time is 12 hours.
[0025] This invention provides a γ-Fe composite Fe-N / O@C catalyst prepared by the aforementioned synthesis method, using a porous carbon material as a support. The outer surface of the support is loaded with a nitrogen / oxygen complex structure of iron and particulate iron nanoclusters. The porous carbon material has a dodecahedral structure with a specific surface area of not less than 100 cm². 2 g -1 (Preferred specific surface area is 342.6 cm²) 2 g -1 The carrier pore size is 2-16 nm (preferably 4 nm).
[0026] This invention also provides a method for applying the γ-Fe composite Fe-N / O@C catalyst to advanced oxidation treatment of wastewater. The Fe-N / O@C catalyst powder is added to a solution containing a certain concentration of target organic pollutants. When adsorption-desorption equilibrium is reached, a certain amount of oxidant is added to carry out the reaction.
[0027] More preferably, the dosage of the Fe-N / O@C catalyst is 0.1–1 g / L.
[0028] More preferably, the concentration of the organic pollutant is 5–20 mg / L.
[0029] More preferably, the oxidant is at least one selected from potassium persulfate, sodium persulfate, sodium hydroxide, sodium persulfate, and potassium persulfate.
[0030] More preferably, the mass ratio of the Fe-N / O@C catalyst to the oxidant is 1:2 to 10.
[0031] Compared with the prior art, the present invention has the following advantages and beneficial effects:
[0032] (1) In this invention, a series of Fe-N / O@C catalysts were prepared by pyrolysis of Fe and O co-doped ZIF-8 nanomaterials. When the obtained Fe-N / O@C was used to activate PMS to degrade organic pollutants, it was found that the Fe-N / O coordination structure was better than that of FeN. x Compared to pure N-doped carbon, Fe-N / O@C exhibits superior catalytic performance, thanks to the synergistic effect of single-atom Fe and γ-Fe species in the N2-Fe-O2 coordination configuration. The prepared Fe-N / O@C demonstrated a peak pollutant removal efficiency of 99.4% within 60 minutes, with a calculated reaction rate 2.29 times that of the Fe-N@C catalyst. Furthermore, Fe-N / O@C exhibits good catalytic activity over a wide pH range of 2.0–10.0, showing promising application prospects in practical wastewater treatment.
[0033] (2) The γ-Fe composite Fe-N / O@C catalyst prepared in this invention has a dodecahedral structure compared with existing catalysts of the same type. The outer surface is supported by a nitrogen / oxygen complex structure of iron and particulate iron nanoclusters. It has a high specific surface area and large pore size, which provides a fast transport channel for ions. This is conducive to the non-radical degradation of organic pollutants in water, reducing the amount of oxidant used and the generation of sulfate ions, thereby reducing the secondary pollution caused by wastewater treatment. The presence of iron nanoclusters makes the catalyst easier to recycle.
[0034] (3) The method for preparing a γ-Fe composite Fe-N / O@C catalyst proposed in this invention has simple equipment, mild reaction conditions, easy process control, no need to add toxic and harmful reagents, and facilitates the industrialization and engineering application of the catalyst. Attached Figure Description
[0035] Figure 1 The images show scanning electron microscope (SEM) images and mapping diagrams of Fe-ZIF-8 and Fe-N / O@C synthesized in Example 1 of this invention.
[0036] Figure 2 The X-ray photoelectron spectrum of Fe-N / O@C-800 synthesized in Example 1 of this invention is shown.
[0037] Figure 3 The Mössbauer spectrum of Fe-N / O@C-800 synthesized in Example 1 of this invention is shown.
[0038] Figure 4 This is a comparison of the degradation effects of Fe-N / O@C-800 in Example 1, Fe-N@C-800 in Comparative Example 1, and N@C-800 in Comparative Example 2.
[0039] Figure 5 For the present invention in different Zn 2+ Comparison of degradation effects between Fe-N / O@C catalyst synthesized with methanol and Fe-N / O@C catalyst synthesized with methanol.
[0040] Figure 6 This paper compares the degradation effects of the Fe-N / O@C catalyst synthesized at different calcination temperatures according to the present invention.
[0041] Figure 7 This paper compares the degradation effects of the Fe-N / O@C catalyst synthesized in this invention on PMS under different initial pH conditions.
[0042] Figure 8 This paper compares the degradation effects of the Fe-N / O@C catalyst synthesized in this invention under different oxidant conditions.
[0043] Figure 9Evaluation of the recycling performance of the Fe-N / O@C catalyst synthesized in this invention.
[0044] Figure 10 This is a comparison of the Fe 2p XPS spectra of the Fe-N / O@C catalyst synthesized in this invention before and after the reaction. Detailed Implementation
[0045] The specific embodiments of the present invention will be further described below. It should be noted that the description of the embodiments is for the purpose of aiding understanding the present invention, but does not constitute a limitation thereof. Furthermore, the technical features involved in the various embodiments of the present invention described below can be combined with each other as long as they do not conflict with each other.
[0046] Example 1
[0047] 0.241 g (0.5 mmol) of ferrous gluconate and 2.14 g of zinc nitrate hexahydrate were dissolved in 44.5 mL of methanol and labeled as solution A. 4.72 g of 2-methylimidazole was dissolved in another beaker of 44.5 mL of methanol and labeled as solution B. Solutions A and B were stirred separately with a glass rod until completely dissolved. Solution B was then poured into solution A, and the mixture was stirred on a magnetic stirrer for 2 h. After stirring, the solution was allowed to stand for 20 h, washed three times with methanol, and the precipitate was centrifuged and dried under vacuum at 60 °C overnight to obtain the Fe-ZIF-8 precursor. The obtained Fe-ZIF-8 was then placed in a quartz boat and placed in a tube furnace. Nitrogen gas was then introduced into the tube furnace, and the temperature was increased to 800 °C at a rate of 5 °C / min and maintained for 3 h. After the tube furnace cooled down, the sample was taken out and soaked in 0.5 mol / L HCl for 2 h, centrifuged, washed with methanol, and then dried in a vacuum drying oven at 60 ℃ for 12 h to obtain Fe-N / O@C-800.
[0048] Comparative Example 1
[0049] 0.293 g (0.5 mmol) of phthalocyanine iron and 2.14 g of zinc nitrate hexahydrate were dissolved in 44.5 mL of methanol and labeled as solution A. 4.72 g of 2-methylimidazole was dissolved in another beaker of 44.5 mL of methanol and labeled as solution B. Solutions A and B were stirred separately with a glass rod until completely dissolved. Solution B was then poured into solution A, and the mixture was stirred on a magnetic stirrer for 2 h. After stirring, the solution was allowed to stand for 20 h, washed three times with methanol, and the precipitate was centrifuged and dried under vacuum at 60 °C overnight to obtain the Fe-ZIF-8 precursor. The obtained Fe-ZIF-8 was then placed in a quartz boat and placed in a tube furnace. Nitrogen gas was then introduced into the tube furnace, and the temperature was increased to 800 °C at a rate of 5 °C / min and maintained for 3 h. After the tube furnace cooled down, the sample was taken out and soaked in 0.5 mol / L HCl for 2 h, centrifuged, washed with methanol, and then dried in a vacuum drying oven at 60 ℃ for 12 h to obtain Fe-N@C-800.
[0050] Comparative Example 2
[0051] 2.14 g of zinc nitrate hexahydrate was dissolved in 44.5 mL of methanol and labeled as solution A; 4.72 g of 2-methylimidazole was dissolved in another beaker of 44.5 mL of methanol and labeled as solution B. Solutions A and B were stirred separately with glass rods until completely dissolved. Solution B was then poured into solution A, and the mixture was stirred on a magnetic stirrer for 2 hours. After stirring, the solution was allowed to stand for 20 hours, washed three times with methanol, and the precipitate was centrifuged and dried under vacuum at 60 °C overnight to obtain the Fe-ZIF-8 precursor. The obtained Fe-ZIF-8 was then placed in a quartz boat and placed in a tube furnace. Nitrogen gas was then introduced into the tube furnace, and the temperature was increased to 800 °C at a rate of 5 °C / min and maintained for 3 hours. After the tube furnace cooled down, the sample was taken out and soaked in 0.5 mol / L HCl for 2 h, centrifuged, washed with methanol, and then dried in a vacuum drying oven at 60 ℃ for 12 h to obtain N@C-800.
[0052] Figure 1 SEM studies revealed the morphological and structural information of the material synthesized in Example 1. (a) is the SEM image of the Fe-ZIF-8 precursor, and (b) is the SEM image of Fe-N / O@C. It can be seen that the obtained Fe-N / O@C has the rhombic dodecahedral shape of ZIF-8 before and after calcination, and the clusters of iron nanoparticles are clearly visible on the surface. Figure 1 Images (c1) to (c4) show the elemental distribution on the surface of the Fe-N / O@C material, detected by surface elemental mapping. The four elements are uniformly distributed on the Fe-N / O@C material surface, confirming the successful doping of Fe and O. Simultaneously, the nitrogen isotherm adsorption-desorption curves of the Fe-N / O@C material were measured. Figure 1 As can be seen from (d) and (e), due to Fe doping, the specific surface area of the calcined material is approximately 342.6 cm². 2 The material has a pore size of approximately 4 nm, which gives it excellent adsorption properties, making it more conducive to the degradation of organic pollutants.
[0053] X-ray photoelectron spectroscopy (XPS) was used to... Figure 2 ) and Mössbauer spectrum ( Figure 3 To further analyze the internal structure of the Fe-N / O@C catalyst synthesized in Example 1, the N 1s spectrum was analyzed. The N 1s spectrum showed the presence of multiple types of N species in Fe-N / O@C, namely pyridine nitrogen (398 eV), Fe-N x The chromatograms show the following nitrogen states: (399.0 eV), pyrrole nitrogen (400.2 eV), graphitic nitrogen (401.5 eV), and oxidized nitrogen (404.5 eV). A characteristic peak corresponding to the Fe-O bond (531.0 eV) is present in the O1s XPS spectrum, while characteristic peaks at 707.5 eV, 720.5 eV, 710.9 eV, 723.6 eV, 713.1 eV, and 725.7 eV are observed in the Fe 2p spectrum, corresponding to Fe... 0 2p 1 / 2 Fe 0 2p 3 / 2 Fe 3+ 2p 1 / 2 Fe 3+ 2p 3 / 2 Fe 2+ 2p 1 / 2 and Fe 2+ 2p 1 / 2 In Mössbauer spectroscopy, singlets correspond to γ-Fe species, while doublets represent O2-Fe-N2 species. These characterization results demonstrate the presence of γ-Fe and single-atom O2-Fe-N2 sites in the synthesized material, confirming that the synthesized material is a γ-Fe composite Fe-N / O@C catalyst.
[0054] Example 2
[0055] This embodiment tested the catalytic performance of Fe-N / O@C-800 from Example 1, Fe-N@C-800 from Comparative Example 1, and N@C-800 from Comparative Example 2 in degrading target organic pollutants (bisphenol A, BPA). The specific procedures were as follows: Fe-N / O@C-800 from Example 1, Fe-N@C-800 from Comparative Example 1, and N@C-800 from Comparative Example 2 were added to solutions containing 10 mg / L of the target organic pollutant. When adsorption-desorption equilibrium was reached, 0.4 g / L of PMS was added to initiate the reaction.
[0056] like Figure 4 As shown, PMS alone exhibited a low degradation rate of only 17.3%, indicating that its ability to remove organic pollutants from water through PMS self-decomposition is quite limited. In contrast, the addition of N@C-800 slightly improved the degradation rate to 38%. When Fe was doped into the material, the degradation efficiency of the Fe-N@C-800 / PMS system was greatly improved, reaching 94.5%, which fully demonstrates the excellent PMS activation performance of trace FeN4 sites. After introducing O atoms into the Fe-N4 structure, Fe-N / O@C-800 with an O2-Fe-N2 coordination structure showed a higher degradation efficiency (99.4%) than Fe-N@C-800. Simultaneously, the degradation rate constant of the Fe-N / O@C-800 / PMS system reached 0.109 min⁻¹. -1 Under the same conditions, the Fe-N@C-800 / PMS system (0.047 min) -1 The degradation performance of Fe-N / O@C catalyst is 2.28 times that of γ-Fe. The above comparison illustrates that the excellent degradation performance of Fe-N / O@C catalyst is due to the synergistic effect of single-atom Fe and γ-Fe species in the N2-Fe-O2 coordination configuration.
[0057] Example 3
[0058] To further analyze different Zn 2+ The effect of the ratio of Zn to methanol on the degradation performance of the synthesized Fe-N / O@C catalyst was investigated. Following the preparation method in Example 1, the ratio of Zn to methanol was adjusted. 2+ Fe-N / O@C catalysts synthesized at molar ratios of 1:150, 1:300, and 1:600 with methanol were added to 100 mL of bisphenol A (BPA) solution and reacted in 250 mL blue-capped flasks. The controlled reaction conditions were: catalyst dosage 0.1 g / L, contaminant concentration 10 mg / L, and persulfate (PMS) concentration 0.4 g / L. Figure 5 As shown, the results indicate that the three selected Zn... 2+ The Fe-N / O@C catalysts synthesized with methanol at ratios of 1:150, 1:300, and 1:600 all achieved pollutant removal rates of over 90% within 60 minutes.
[0059] Example 4
[0060] To further analyze the effect of Fe-N / O@C materials calcined at different temperatures on the activation performance of PMS, following the preparation method in Example 1, Fe-N / O@C catalysts synthesized at calcination temperatures of 700℃, 800℃, and 900℃ were added to 100 mL of bisphenol A (BPA) solution and reacted in 250 mL blue-capped flasks. The reaction conditions were controlled as follows: catalyst dosage 0.1 g / L, contaminant concentration 10 mg / L, and persulfate (PMS) concentration 0.4 g / L. Figure 6 As shown, the results indicate that the Fe-N / O@C catalysts synthesized at the three selected calcination temperatures (700℃, 800℃ and 900℃) can all achieve a pollutant removal rate of more than 80% within 60 min. When the calcination temperature is 800℃, 100% removal of pollutants can be achieved in 40 min, indicating that 800℃ is the optimal calcination temperature.
[0061] Example 5
[0062] To further analyze the effect of Fe-N / O@C material on the activation performance of PMS under different initial pH conditions, the Fe-N / O@C catalyst prepared in Example 1 was added to bisphenol A (BPA) solutions with initial pH values of 2.0, 6.0, 8.0, and 10.0, respectively, and reacted in 250 mL blue-capped flasks. The controlled reaction conditions were: catalyst dosage 0.1 g / L, contaminant concentration 10 mg / L, and PMS concentration 0.4 g / L. Figure 7 As shown, the results indicate that within a wide pH range of 2.0 to 10.0, the removal rate of the target pollutant by Fe-N / O@C / PMS is close to 100% within 60 min. This demonstrates that the catalyst prepared in this invention can resist interference from environmental background factors and remain stable over a wide pH range when degrading recalcitrant organic pollutants in wastewater, thus meeting the needs of wastewater treatment to a certain extent.
[0063] Example 6
[0064] To further analyze the effect of Fe-N / O@C material on the activation performance of different oxidants, the Fe-N / O@C catalyst prepared in Example 1 was added to a solution of 2-fluorophenol (2-FP) and reacted in a 250 mL blue-capped flask. The reaction was controlled under the following conditions: catalyst dosage 0.1 g / L, contaminant concentration 10 mg / L, and dosages of sodium persulfate, sodium persulfate, and hydrogen peroxide 1 g / L. Figure 8 As shown, the results indicate that the Fe-N / O@C catalyst can effectively activate various oxidants (including PDS, PMS and H2O2) to achieve a removal rate of over 90% for the target organic pollutants within 60 min.
[0065] Example 7
[0066] To further investigate the cycling stability of the Fe-N / O@C material, the Fe-N / O@C catalyst prepared in Example 1 was subjected to an organic pollutant removal cycling experiment. The results are as follows: Figure 9 As shown, the catalyst can be reused after each reaction by simple solid-liquid separation and drying, without any further treatment. The Fe-N / O@C removal rate remained at 91.8% after four cycles, indicating that the prepared catalyst has good cycling stability.
[0067] Example 8
[0068] To further analyze the active sites of the Fe-N / O@C material of this invention, fine peak separation was performed on the XPS spectra of Fe 2p before and after the reaction, as shown below. Figure 10 As shown, the results indicate that after the reaction, Fe 0 The 2p peaks (707 eV and 720 eV) showed a significant decrease, indicating a reduction in γ-Fe content, which weakened its synergistic effect with the O2-Fe-N2 site, leading to a decrease in catalytic activity. Meanwhile, Fe... 3+ / Fe 2+ The concentration decreased from 1.03 before the reaction to 0.79, indicating the presence of Fe. 3+ and Fe 2+ The redox cycle gives Fe-N / O@C strong catalytic activity and cycling performance.
[0069] Example 9
[0070] 0.121 g (0.25 mmol) of ferrous gluconate and 2.14 g of zinc nitrate hexahydrate were dissolved in 44.5 mL of methanol and labeled as solution A. 4.72 g of 2-methylimidazole was dissolved in another beaker of 44.5 mL of methanol and labeled as solution B. Solutions A and B were stirred separately with a glass rod until completely dissolved. Solution B was then poured into solution A, and the mixture was stirred on a magnetic stirrer for 2 hours. After stirring, the solution was allowed to stand for 20 hours. The solution was washed three times with methanol, centrifuged to remove the precipitate, and then vacuum-dried overnight at 60 °C to obtain the Fe-ZIF-8 precursor. The obtained Fe-ZIF-8 was then placed in a quartz boat and placed in a tube furnace. Nitrogen gas was then introduced into the tube furnace, and the temperature was increased to 800 °C at a rate of 5 °C / min and maintained for 3 hours. After the tube furnace cooled down, the sample was taken out and soaked in 0.5 mol / L HCl for 2 h, centrifuged, washed with methanol, and then dried in a vacuum drying oven at 60 ℃ for 12 h to obtain Fe-N / O@C.
[0071] Example 10
[0072] 0.241 g (0.5 mmol) of ferrous gluconate and 2.14 g of zinc nitrate hexahydrate were dissolved in 22.5 mL of methanol and labeled as solution A. 4.72 g of 2-methylimidazole was dissolved in another beaker of 22.5 mL of methanol and labeled as solution B. Solutions A and B were stirred separately with a glass rod until completely dissolved. Solution B was then poured into solution A, and the mixture was stirred on a magnetic stirrer for 2 hours. After stirring, the solution was allowed to stand for 20 hours. The solution was washed three times with methanol, centrifuged to remove the precipitate, and then vacuum-dried overnight at 60 °C to obtain the Fe-ZIF-8 precursor. The obtained Fe-ZIF-8 was then placed in a quartz boat and placed in a tube furnace. Nitrogen gas was then introduced into the tube furnace, and the temperature was increased to 800 °C at a rate of 5 °C / min and maintained for 3 hours. After the tube furnace cooled down, the sample was taken out and soaked in 0.5 mol / L HCl for 2 h, centrifuged, washed with methanol, and then dried in a vacuum drying oven at 60 ℃ for 12 h to obtain Fe-N / O@C.
[0073] Finally, it should be noted that the above embodiments are merely preferred embodiments of the present invention and are only used to explain the present invention, not to limit the present invention. For those skilled in the art, modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some of the technical features. Any changes, substitutions, and modifications made within the spirit and principles of the present invention should be included within the protection scope of the present invention.
Claims
1. A γ-Fe composite Fe-N / O@C catalyst, characterized in that, The γ-Fe composite Fe-N / O@C catalyst contains γ-Fe and single-atom O2-Fe-N2 sites, wherein the single-atom Fe and γ-Fe species in the N2-Fe-O2 coordination configuration form a synergistic effect. The preparation method of the γ-Fe composite Fe-N / O@C catalyst includes the following steps: S1. Dissolve ferrous gluconate and zinc nitrate hexahydrate in methanol and label it as solution A; dissolve 2-methylimidazole in methanol in another beaker and label it as solution B; stir solutions A and B separately with a glass rod until they are completely dissolved, then pour solution B into solution A and stir on a magnetic stirrer. After stirring, let the solution stand and age, wash with methanol, centrifuge the precipitate, and then vacuum dry to obtain the Fe-ZIF-8 precursor. S2. The obtained Fe-ZIF-8 precursor was placed in a quartz boat, and then the quartz boat was placed in a tube furnace. Nitrogen gas was then introduced into the tube furnace and the temperature was raised for calcination. S3. After the tube furnace cools down, the sample is taken out and soaked in hydrochloric acid, centrifuged, washed with methanol, and then dried in a vacuum drying oven to obtain the Fe-N / O@C catalyst.
2. The γ-Fe composite Fe-N / O@C catalyst according to claim 1, characterized in that, In step S1, the molar ratio of ferrous gluconate and zinc nitrate hexahydrate is 1:70~150; the molar ratio of zinc nitrate hexahydrate to methanol is 1:150~600; and the molar ratio of 2-methylimidazole to methanol is 1:8~40.
3. The γ-Fe composite Fe-N / O@C catalyst according to claim 1, characterized in that, In step S1, the stirring time is 1-4 h; the settling and aging time is 12-24 h.
4. The γ-Fe composite Fe-N / O@C catalyst according to claim 1, characterized in that, In step S1, the vacuum drying temperature is 60~80℃ and the vacuum drying time is 12~24 h.
5. The γ-Fe composite Fe-N / O@C catalyst according to claim 1, characterized in that, In step S2, the heating rate is 2~10℃ / min; the calcination temperature is 700~900℃; and the calcination time is 2~4 h.
6. The γ-Fe composite Fe-N / O@C catalyst according to claim 1, characterized in that, In step S3, the tube furnace is cooled to room temperature at a rate of 2~10℃ / min; the vacuum drying temperature is 60~80℃, and the vacuum drying time is 12~24h.
7. The γ-Fe composite Fe-N / O@C catalyst according to claim 1, characterized in that, Using porous carbon material as a carrier, the outer surface of the carrier is loaded with a nitrogen / oxygen complex structure of iron and particulate iron nanoclusters. The porous carbon material has a dodecahedral structure with a specific surface area of not less than 100 cm². 2 g -1 The carrier has a pore size of 2-16 nm.
8. The application of the γ-Fe composite Fe-N / O@C catalyst according to claim 1 in the removal of organic pollutants from water using advanced oxidation technologies.
9. The application according to claim 8, characterized in that, The γ-Fe composite Fe-N / O@C catalyst powder was added to a solution containing the target organic pollutant. When the adsorption-desorption equilibrium was reached, an oxidant was added to initiate the reaction.
10. The application according to claim 9, characterized in that, The dosage of the Fe-N / O@C catalyst is 0.1~1 g / L; the concentration of the organic pollutant is 5~20 mg / L; the oxidant is at least one of potassium persulfate, sodium persulfate, sodium persulfate and potassium persulfate; the mass ratio of the Fe-N / O@C catalyst to the oxidant is 1:2~10.
Citation Information
Patent Citations
Preparation method and application of alpha or gamma-Fe modified Fe-N-C material
CN116651483A
